Abnormal hemostasis in children with vascular anomalies, part I: Thrombocytopenias among different vascular anomalies. Issue 196 (December 2020) - Tole, Soumitra; Price, Victoria; Pope, Elena; Powell, Julie; David, Michèle; Zwicker, Kelley; Kendrick, Victoria; Malic, Claudia; John, Philip R.; Somers, Gino R.; Dubois, Josée; Brandão, Leonardo R.
Abstract: Long before the classification of vascular anomalies from the International Society for the Study of Vascular Anomalies (ISSVA) provided a framework to differentiate vascular anomalies, otherwise known as vascular birthmarks, it was recognized that patients with such lesions can present with acute life-threatening hemostatic and/or thrombotic complications, as well as chronic long-standing bleeding or thrombotic issues. Scenarios such as a rapidly growing vascular lesion with severe acute thrombocytopenia, a visceral hemorrhagic lesion, a lesion associated with repetitive and painful superficial thrombosis, and cases of unprovoked or post-procedural fatal pulmonary embolism highlight the wide spectrum of manifestations of abnormal coagulation in patients with vascular anomalies. The separation of vascular anomalies into two distinct groups, vascular tumors and vascular malformations, was followed by the characterization that their respective coagulopathies were due to either a derangement of platelets or to a disequilibrium of the patient's coagulation/fibrinolytic process. This configuration of coagulopathies will be the foundation for this two-chapter review series. In the initial review, coagulopathies where thrombocytopenia is the main feature will be characterized, whereas the second review will focus on vascular malformations that have a coagulation disorder secondary to some degree of coagulation consumption and/or fibrinolytic pathway derangement. Highlights: Patients with vascular anomalies, otherwise known as birth marks, can present with acute life-threatening hemostatic and/or thrombotic complications, as well as chronic long-standing bleeding or thrombotic issues. The separation of vascular anomalies into two distinct groups, vascular tumors and vascular malformations, was followed by the characterization that their respective coagulopathies were due to either a derangement of platelets or to a disequilibrium of the patient's coagulation/fibrinolytic process. Part I of this two-part review will focus on coagulopathies in children with vascular anomalies where thrombocytopenia is the main feature.